Gauging the Impact of Higher Capital and Oil Costs on Potential Output - Cournède, Boris (OECD Economics Department Working Papers, 2010)
The 2007-2009 period has been characterised by an oil shock followed by a financial crisis. Higher oil prices and the prospect of higher borrowing costs are likely to reduce the productive potential of OECD economies. The present study provides illustrative numerical estimates of the impact under different scenarios using a stylised model based on a production function. In a scenario where real borrowing costs for firms return to their 1991-2001 average as opposed to staying at the level at which the capital stock in place at the end of 2007 had been invested, the impact on equilibrium GDP could be in the order of 2%. If the real oil price stays at $80 per barrel, up from the $50 average at which the capital stock in place in 2007 had been invested, the impact on equilibrium GDP could be in the order of 1%